EFEKTIVITAS KAFĀ’AH MEMBENTUK RUMAH TANGGA HARMONIS PERSPEKTIF UNDANG-UNDANG NO. 1 TAHUN 1974 - Asrizal Asrizal (JOURNAL EQUITABLE, 2018)
Regulations and hadith texts explain there is no prohibition to marry when both are equal. Equality is a concept of equivalence between the couples who want to get married to get a sakina, affection and mercy family. In this concept, religious elements is the main and most important in equality. While the others just as a supporting factor, such as: education, offspring, position and economic degree. In determining the partner, every one should be understood the equality concepts and criteria in integrated, inductive and comprehensive, what intended to avoid mistakes in choosing a good couple. In this article, the author examine about: the equality relevance on household harmony in terms of normative and juridical value.